2021
DOI: 10.5267/j.ccl.2021.4.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some new 6-aryl-3-(4-isopropylphenyl)[1,2,4]triazolo[3,4-b][1,3,4] thiadiazoles and its anti-microbial study

Abstract: New series of fused 1,2,4-triazoles, i.e., 3-(4-isopropylphenyl)-6-substituted phenyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles (5a-5j) have been synthesized via a four-step procedure and using eco-friendly reaction condition at some steps of the synthesis. It was adopted by the formation of hydrazide of methyl 4-isopropylbenzoate (1) followed by reaction with CS2 in basic media to afford potassium salt, which on cyclized to our essential step, 4-amino-5-(4-isopropylphenyl)-4H-1,2,4-triazole-3-thiol (4). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The electronic properties of nitrogen or sulfur heteroatoms are a significant factor in their selection. One of these compounds, 1,2,4-triazole, has demonstrated a wide range of biological activities such as antibacterial, [5][6][7] antimicrobial, [8][9][10] anti-HIV, [11][12][13] antiviral, [14,15] antitumor, [14][15][16] and antitubercular. [17][18][19][20] Researchers have found that modifying the structure of the triazole moiety with specific molecular groups can enhance its biological potency.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic properties of nitrogen or sulfur heteroatoms are a significant factor in their selection. One of these compounds, 1,2,4-triazole, has demonstrated a wide range of biological activities such as antibacterial, [5][6][7] antimicrobial, [8][9][10] anti-HIV, [11][12][13] antiviral, [14,15] antitumor, [14][15][16] and antitubercular. [17][18][19][20] Researchers have found that modifying the structure of the triazole moiety with specific molecular groups can enhance its biological potency.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of triazoles and their biological importance have received considerable attention in recent years, and this class of compounds have become one of the potential agents for drug discovery. Among these, 1,2,4-triazoles represent an important class of organic compounds with wide use in medicine, agriculture, and industry . A wide variety of therapeutically interesting drug candidates possessing analgesic, anti-inflammatory, anti-microbial, anti-cancer, anti-depressant, anti-fungal, anti-convulsant, and anti-viral activities are discussed in the literature possessing the 1,2,4-triazole moiety. …”
Section: Introductionmentioning
confidence: 99%